A comparison of online and in-person counseling outcomes using solution-focused brief therapy for college students with anxiety. Issue 4 (19th May 2022) - Novella, Jocelyn K.; Ng, Kok-Mun; Samuolis, Jessica
Abstract: Objective This study compared online, synchronous video counseling to in-person counseling using solution-focused brief therapy for college students with mild to moderate anxiety. Participants: Participants were 49 undergraduate students who were seeking counseling for mild to moderate anxiety. The study was conducted from November, 2017 to December 2018. Methods: In a randomized, non-inferiority design, undergraduate participants were randomly assigned to online, synchronous video counseling or in-person treatment for anxiety using solution-focused brief therapy (SFBT). Participants completed the Beck's Anxiety Inventory (BAI) and College Counseling Assessment of Psychological Symptoms (CCAPS) to assess outcomes. Results: The results showed significant changes in scores on the BAI and the CCAPS Generalized Anxiety and Social Anxiety subscales for participants in both study conditions, and no significant differences in effectiveness of the two delivery methods. Conclusions: The findings provide support for the treatment of college students with anxiety with SFBT through online, synchronous video counseling. Limitations related to sample size and diversity are discussed.